Malpractices in Nigeria's Fourth Republic elections: Challenges of democratic governance - Isma'ila, Yusuf (2016)
Scholars tend to analyse increasing transitions to democracy over the past four decades, particularly on the significance of conducting fair elections and the impacts on democratic transition process in Nigeria. Indeed, there is a need to study challenges of electoral malpractices since the emergence of Nigeria's Fourth Republic in 1999. Therefore, this study aims to identify electoral malpractices occurred in the last sixteen years in Nigeria that posed threats against the elected democratic governance. In addition, the impacts of these electoral malpractices are also critically analysed. Qualitative research method is adopted in this study, in which both primary and secondary data were used in conducting the research. The target respondents interviewed through purposive sampling technique involve Nigerian politicians, electoral officers, non-governmental organizations and the academia. The findings reveal that the challenges of electoral malpractices have significantly influenced Nigeria's Fourth Republic governance. The study also highlights that insecurity, corruption, weak democratic institutions, lack of internal democracy within political parties, military mentality, weak electoral umpire and electoral irregularities have seriously posed threats on democratic practices. This study concludes that those threats have undermined democratic transition and aspiration for democratic governance. The study recommends strengthening democratic institutions, improving electoral reforms, addressing corruption, poverty, prosecuting electoral offenders and enhancing participation of electorates in promoting fair election for sustainable democracy.